Avaliação de interação e clivagem de DNA por complexos de rutênio - Martins, Patrícia Helenita Rocha (2014)
Studies have shown that the ruthenium complexes have less toxicity than the presently used drugs. Then that complexes are being as antitumor agents, some of which can be photoactivated and can be used in photodynamic therapy. Based on these studies we used two ruthenium complexes, cis- [Ru (bpy)2 (SO3) (NO)] (PF6)] (A) and cis- [Ru (bpy)2 (SO3) (H2O)] (B), where its action will be compared due to the difference in the binder, it is known that ruthenium complex nitrosylated are being studied because of the action of the binder NO in biological systems. The experiments employing electrophoresis showed the activity of interaction / cleavage of the complex with ADN, only when irradiated and dependent on the concentration of the complexes. The reactivity tests with hydrogen peroxide have also shown effects of ADN cleavage in the absence and presence of light. The use of radical inhibitors suggested that the mechanism of interaction between A and B complex and the ADN is oxidative, because oxidative species identification. The addition of NaCl to verify the complex interaction mechanism, allowed to state the two complex under study are electrostatic interactions with the ADN. They used two groove binders, which suggests interaction through the major groove of the complex, however it is unclear whether occurring interaction also a minor groove, and the B complex found that the complex shows no selectivity, may bind by two grooves. UV tests show changes in the bands of the complex, which may indicate complex interaction of A and B. The tests exclusion column show the bands indicating interaction between the complex and ADN. The determination Kb 1.31 x 105 M-1 (A) and 3.77 x 104 M-1 (B) showed that the complexes bind to ADN and are within the range found for the complex to exhibit interaction. The viscosimetry experiment indicated the occurrence of electrostatic interaction between the complexes. The AFM test showed that the complexes A and B changed the conformation of ADN, indicating interaction. The EPR technique showed the appearance of free radicals in the presence of the complex and H2O2 even without irradiation.